The N terminus of the small heat shock protein HSPB7 drives its polyQ aggregation–suppressing activity - Wu, Di (J Biol Chem, 2019)
Heat shock protein family B (small) member 7 (HSPB7) is a unique, relatively unexplored member within the family of human small heat shock proteins (HSPBs). Unlike most HSPB family members, HSPB7 does not oligomerize and so far has not been shown to associate with any other member of the HSPB family. Intriguingly, it was found to be the most potent member within the HSPB family to prevent aggregation of proteins with expanded polyglutamine (polyQ) stretches. How HSPB7 suppresses polyQ aggregation has remained elusive so far. Here, using several experimental strategies, including in vitro aggregation assay, immunoblotting and fluorescence approaches, we show that the polyQ aggregation-inhibiting activity of HSPB7 is fully dependent on its flexible N-terminal domain (NTD). We observed that the NTD of HSPB7 is both required for association with and inhibition of polyQ aggregation. Remarkably, replacing the NTD of HSPB1, which itself cannot suppress polyQ aggregation, with the NTD of HSPB7 resulted in a hybrid protein that gained anti-polyQ aggregation activity. The hybrid NTD(HSPB7)–HSPB1 protein displayed a reduction in oligomer size and, unlike WT HSPB1, associated with polyQ. However, experiments with phospho-mimicking HSPB1 mutants revealed that de-oligomerization of HSPB1 alone does not suffice to gain polyQ aggregation–inhibiting activity. Together, our results reveal that the NTD of HSPB7 is both necessary and sufficient to bind to and suppress the aggregation of polyQ-containing proteins.